Friday
March 24, 2017

Post a New Question

Posted by on Sunday, October 2, 2011 at 2:24am.

Expand and simplify

1.(9a-3)^2

2.(x^2+2x-1)^2

3. 2(3a+4)(a-6)-(3-a)^2+4(5-a)

  • Math - , Sunday, October 2, 2011 at 11:53pm

    [3(3a-1)]^2 = 9(9a^2 - 6a + 1) = 81a^2 - 54a + 9

    don't know which you'd consider simpler

    same with this one. expand it and get a 4th degree polynomial.

    2(3a+4)(a-6) - (3-a)^2 + 4(5-a)
    = 2(3a^2 - 14a -24) - (9 - 6a + a^2) + 20 - 4a
    = 6a^2 - 28a - 48 - 9 + 6a - a^2 + 20 - 4a
    = 5a^2 - 26a - 37

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question